2020
DOI: 10.1002/pon.5305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic cancer risk assessment: A screenshot of the psychosocial profile of women at risk for hereditary breast and ovarian cancer syndrome

Abstract: Objective: There is a lack of information describing Brazilian women at risk of hereditary breast and ovarian cancer syndrome (HBOC) who undergo genetic cancer risk assessment (GCRA). This study aims to characterize the psychosocial profile of women at risk for HBOC at their first GCRA to obtain an overview of their families' profiles and the challenges of the oncogenetics setting.Methods: This was a cross-sectional study in which interviews were conducted with 83 cancer-affected women at their first GRCA appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Este achado tem como hipótese que o Brasil concentra um volume maior de publicações por parte dos pesquisadores, uma vez que estas ferramentas são de uso cotidiano, principalmente na Atenção Primária à Saúde, e com registro nos prontuários individuais e familiares por parte das Equipes de Estratégia de Saúde da Família. Apesar de não possuir um número elevado de publicações que trazem o genograma e ecomapa como foco central das pesquisas, existem outros estudos que fazem uso das ferramentas como objeto secundário para auxiliar a construção das propostas metodológicas aplicadas [7][8][9][10][11][12].…”
Section: Discussionunclassified
“…Este achado tem como hipótese que o Brasil concentra um volume maior de publicações por parte dos pesquisadores, uma vez que estas ferramentas são de uso cotidiano, principalmente na Atenção Primária à Saúde, e com registro nos prontuários individuais e familiares por parte das Equipes de Estratégia de Saúde da Família. Apesar de não possuir um número elevado de publicações que trazem o genograma e ecomapa como foco central das pesquisas, existem outros estudos que fazem uso das ferramentas como objeto secundário para auxiliar a construção das propostas metodológicas aplicadas [7][8][9][10][11][12].…”
Section: Discussionunclassified
“…The operational framework of the OD entails an initial appointment for CGC, with two parts: the first part conducted by a nurse, involving the collection of sociodemographic data, patients’ cancer history, and pertinent familial information to construct pedigrees; the second part comprises a consultation with a medical geneticist, wherein the GT and its implications are deliberated upon. Exhaustive details regarding all OD processes and protocols have been documented in prior publications ( Palmero et al, 2016 ; Campacci et al, 2020 ). A total of 60 women were included and responded to all questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Te majority (n � 31) of the studies reported collecting data in the community (i.e., homes of the participants, private ofces, or workplaces) [41-45, 49, 51, 54, 56, 57, 61, 67, 70-73, 75, 76, 78, 82, 84, 86, 90, 92-95, 97, 102, 103, 105], or an outpatient clinic (n � 6) [46,48,64,65,98] or inpatient unit (n � 5) [47,52,62,91,100] was cited. Less often reported was a community health center (n � 2) [60,104], residential care (n � 2) [18,55], hospice (n � 1) [22], school (n � 1) [101], and a virtual platform (n � 1) [88].…”
Section: Study Settingmentioning
confidence: 99%